2020
DOI: 10.1007/s13197-020-04423-4
|View full text |Cite
|
Sign up to set email alerts
|

Beans germination as a potential tool for GABA-enriched tofu production

Abstract: Gamma-aminobutyric acid (GABA) is an inhibitory neurotransmitter that can be found in many plants, especially beans. Beans are normally used for producing vegetarian foods, such as bean milks, bean sprouts, and tofu. Thus, the aims of this study were to determine the GABA content in various germinated beans (yellow beans, black beans, green beans, and red beans) as well in tofu products made from different types of germinated beans. The results showed that soaking and germination significantly contributed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(32 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, it is important to observe the changing patterns of GABA during germination using quinoa varieties with different GABA contents. Numerous studies have shown that the GABA content of seeds such as buckwheat, soybean , beans, and brown rice increase remarkably after germination. In our work, the results of changes in the GABA content during quinoa germination were similar to those of the previous study .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to observe the changing patterns of GABA during germination using quinoa varieties with different GABA contents. Numerous studies have shown that the GABA content of seeds such as buckwheat, soybean , beans, and brown rice increase remarkably after germination. In our work, the results of changes in the GABA content during quinoa germination were similar to those of the previous study .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies about GABA biosynthesis have mainly focused on the GABA shunt, , only a few reports on the polyamine degradation pathways . Plants are able to accumulate a large amount of GABA through the polyamine degradation pathway to resist stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immersion of beans and cereals seeds in solution could release dormancy and restore physiological functions. Previous studies have demonstrated that different soaking conditions have varying effects on GABA enrichment in germinating beans ( 16 , 29 ). In the present study, when the soaking time was <16 h, GABA contents in adzuki beans increased as soaking time increased ( Figure 1A ), which indicated that metabolism was induced following water imbibition, in addition to the activation of endogenous enzymes and GAD in the reaction system produces GABA secondary metabolites and other nutrients ( 7 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FSF such as natto, miso, tauco, gochujang, douchi, cheonggukjang, doenjang, tofu, tempeh, meju, and bean curd are commercially available in retail markets across the East and Southeast Asian countries like Japan, China, Indonesia, and Korea. Some soybean foods like tofu are also available in countries like the USA and India (Chen et al 2012 ; Vann et al 2020 ). These commercially available fermented foods are fermented by using starter cultures such as Bacillus subtilis for preparing kinema, tungrymbai, bekang, and natto (Tamang 2015 ).…”
Section: Introductionmentioning
confidence: 99%